Economic Feasibility Analysis of Coconut Oil Business in Patampanua Village, Matakali District - Junaedi Y; Aulia, Aulia Nurul Hikmah; Hamsah (Tarjih : Agribusiness Development Journal, 2025)
Patampanua Village has great potential in developing the coconut oil industry because of the community's experience and skills in processing coconuts. However, the traditional methods limit the added value of the product. Therefore, a comprehensive economic analysis is needed to determine the feasibility and potential of this business. This study aims to analyze the economic feasibility of the coconut oil business in Patampanua Village. The research method used is a quantitative and qualitative method with a saturated sampling technique on 30 coconut oil business actors. We collected data through observation, questionnaires, and documentation, then analyzed using income analysis, R/C Ratio, and Break Even Point (BEP). The results of the analysis show that the coconut oil business has a potential income of IDR 30,793,000 per month and a profit of IDR 16,751,929 per month. The R/C Ratio value of 2.19 indicates that this business has good production efficiency. Break Even Point (BEP) is achieved at a minimum sale of 11 units or IDR 512,046. The obstacles facing this business include the difficulty of getting a stable market and fluctuating raw material prices. Strategies that can be done to increase revenue and profit include building a marketing network, developing marketing strategies, managing raw material prices, and product diversification. The results of this study can be a reference for entrepreneurs and local governments to develop coconut oil businesses in Patampanua Village.